1996
DOI: 10.1111/j.1545-5300.1996.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Pragmatics Is Probably Enough for Now

Abstract: In place of aesthetic, essentialist, or foundational pursuits, family therapy might be better served by simply seeking to be helpful. Within such a perspective, ideas are valued/embraced for their functionality and utility. In the following essay, a critical discussion concerning this pragmatic emphasis is undertaken with illustrative clinical case examples from the Eastside Family Centre in Calgary, Alberta, Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…In an earlier work I described what William James referred to as 'radical empiricism' (Amundson, 1996b). At the time I emphasized the very close parallels between radical empiricism and radical constructivism (p. 476).…”
Section: Why Narrative Therapy Should Visit Empiricism and Pragmatismmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier work I described what William James referred to as 'radical empiricism' (Amundson, 1996b). At the time I emphasized the very close parallels between radical empiricism and radical constructivism (p. 476).…”
Section: Why Narrative Therapy Should Visit Empiricism and Pragmatismmentioning
confidence: 99%
“…A number of articles have been written regarding narrative therapy and tendencies noted therein towards reification, if not replication of modernist agendas (Amundson, 1996b;Amundson et al, 1993Amundson et al, , 1994Bertando, 2000;Dallos and Urry, 1999;Doan, 1998;Minuchin, 1991Minuchin, , 1998Minuchin, , 1999Pocock, 1995). These articles highlight the possibility that narrative progression has taken place in ways similar to the very methods/practices it emerged to challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constructivism and the pragmatist position of William James (Orange, 1995;Amundson, 1996) may help to moderate our contribution to this continual work/play of understanding. The former accepts that our ideas cannot predetermine the response of family members -but they may fit.…”
Section: Privileging the Subjective Experiencementioning
confidence: 99%
“…Against the prevailing and possibly destructive postmodern fundamentalism of the recent past, a new consensus seems to be emerging; some truths can be better than others, and it is worth testing explanatory models against reality to see how well they stand up and how long they last (Orange, 1995). Some therapists have also argued in favour of having a plurality or repertoire of theories available, any of which may turn out to be pragmatically useful in a particular clinical situation (Amundson, 1996). In a previous article, I suggested that doctors can make use of both a biological and social constructionist stance within medical consultations.…”
Section: Evolution and Family Therapy: Clinical And Theoretical Implimentioning
confidence: 99%